A bilayer scaffold prepared from collagen and carboxymethyl cellulose for skin tissue engineering applications. Issue 14 (22nd September 2018) - Kilic Bektas, Cemile; Kimiz, Ilgin; Sendemir, Aylin; Hasirci, Vasif; Hasirci, Nesrin
Abstract: Treatment of chronic skin wound such as diabetic ulcers, burns, pressure wounds are challenging problems in the medical area. The aim of this study was to design a bilayer skin equivalent mimicking the natural one to be used as a tissue engineered skin graft for use in the treatments of problematic wounds, and also as a model to be used in research related to skin, such as determination of the efficacy of transdermal bioactive agents on skin cells and treatment of acute skin damages that require immediate response. In this study, the top two layers of the skin were mimicked by producing a multilayer construct combining two different porous polymeric scaffolds: as the dermis layer a sodium carboxymethyl cellulose (NaCMC) hydrogel on which fibroblasts were added, and as the epidermis layer collagen (Coll) or chondroitin sulfate-incorporated collagen (CollCS) on which keratinocytes were added. The bilayer construct was designed to allow cross-talk between the two cell populations in the subsequent layers and achieves paracrine signalling. It had interconnected porosity, high water content, appropriate stability and elastic moduli. Expression of vascular endothelial growth factor (VEGF), basic-fibroblast growth factor (bFGF) and Interleukin 8 (IL-8), and the production of collagen I, collagen III, laminin and transglutaminase supported the attachment and proliferation of cells on both layers of the construct. Attachment and proliferation of fibroblasts on NaCMC were lower compared to performance of keratinocyte on collagen where keratinocytes created a dense and a stratified layer similar to epidermis. The resulting constructs succesfully mimicked in vitro the natural skin tissue. They are promising as grafts for use in the treatment of deep wounds and also as models for the study of the efficacy of bioactive agents on the skin.